Reversing, Reviving, Regenerating: Pastoralist women restoring rangelands in Kenya, Kyrgzstan and Spain - Flintan, Fiona E.; Ghinassi, C.; Buemi, M. (Rangelands Atlas, 2022)
This film describes how three pastoralist women from different parts of the world are restoring rangelands to improve livelihoods, and benefit the greater society and the environment.